The performance profile: A multi-criteria performance evaluation method for test-based problems - Jaśkowski, Wojciech; Liskowski, Paweł; Szubert, Marcin; Krawiec, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
In test-based problems, solutions produced by search algorithms are typically assessed using average outcomes of interactions with multiple tests. This aggregation leads to information loss, which can render different solutions apparently indifferent and hinder comparison of search algorithms.
Keywords: coevolutionary algorithms; evolution strategies; Othello; Reversi; games; multi-objective analysis